The Implementation of the Mimicry Memorization Method in Arabic Vocabulary Learning at MI Takhassus Darul Ulum - Humaidah, Humaidah; Qomariyah, Nurul; Samoh, Tasneem (Alsina : Journal of Arabic Studies, 2024)
This research aims to describe the application of the mimicry memorization method in vocabulary teaching, analyze its implementation based on the existing characteristics and steps, and identify the advantages and disadvantages of applying this method in vocabulary learning for fifth-grade students at MI Takhasus Darul Ulum. This is a field study using a qualitative descriptive approach. Data collection techniques include observation, interviews, and documentation. For data analysis, the Miles and Huberman model is used, which includes data reduction, data presentation, and conclusion drawing. The results of this study indicate that the application of the mimicry memorization method in vocabulary learning for fifth-grade students at MI Takhasus Darul Ulum involves the processes of listening, speaking, imitating, and memorizing. The advantages include direct acquisition of skills by students, correct pronunciation, ease and enthusiasm in memorizing vocabulary, better understanding of vocabulary material, increased student activity, and improved memory retention of vocabulary. The disadvantages include limited time for learning during the memorization process, lack of student attention to the teacher's speech when the class is noisy, and limited media.